PIAS3 expression in squamous cell lung cancer is low and predicts overall survival. (9th January 2015) - Abbas, Rime; McColl, Karen S.; Kresak, Adam; Yang, Michael; Chen, Yanwen; Fu, Pingfu; Wildey, Gary; Dowlati, Afshin
Abstract: Unlike lung adenocarcinoma, little progress has been made in the treatment of squamous cell lung carcinoma (SCC). The Cancer Genome Atlas (TCGA) has recently reported that receptor tyrosine kinase signaling pathways are altered in 26% of SCC tumors, validating the importance of downstream Signal Transducers and Activators of Transcription 3 (STAT3) activity as a prime therapeutic target in this cancer. In the present report we examine the status of an endogenous inhibitor of STAT3, called Protein Inhibitor of Activated STAT3 (PIAS3), in SCC and its potential role in this disease. We examine PIAS3 expression in SCC tumors and cell lines by immunohistochemistry of a tissue microarray and western blotting. PIAS3 mRNA expression and survival data are analyzed in the TCGA data set. SCC cell lines are treated with curcumin to regulate PIAS3 expression and cell growth. PIAS3 protein expression is decreased in a majority of lung SCC tumors and cell lines. Analysis of PIAS3 mRNA transcript levels demonstrated that low PIAS3 levels predicted poor survival; Cox regression analysis revealed a hazard ratio of 0.57 (95% CI: 0.37–0.87), indicating a decrease in the risk of death by 43% for every unit elevation in PIAS3 gene expression. Curcumin treatment increased endogenous PIAS3 expression and decreased cell growth and viability in Calu‐1 cells, a model of SCC. Our results implicate PIAS3 loss in the pathology of lung SCC and raise the therapeutic possibility of upregulating PIAS3 expression as a single target that can suppress signaling from the multiple receptor tyrosine kinase receptors found to be amplified in SCC. Abstract : PIAS3, an endogenous inhibitor of STAT3 activity, demonstrates low expression in squamous cell lung cancer tumors and predicts poor survival. Restoration of PIAS3 expression in squamous lung cancer cells inhibited cell growth by inducing apoptosis and may therefore represent a therapeutic strategy benefiting a subgroup of squamous cell lung cancer patients.